The Immucillins: Design, Synthesis and Application of Transition- State Analogues - B. Evans, Gary; L. Schramm, Vern; C. Tyler, Peter (Current Medicinal Chemistry, 2015)
Transition-state analysis based on kinetic isotope effects and computational chemistry provides electrostatic potential maps to serve as blueprints for the design and chemical synthesis of transition-state analogues. The utility of these molecules is exemplified by potential clinical applications toward leukemia, autoimmune disorders, gout, solid tumors, bacterial quorum sensing and bacterial antibiotics. In some cases, transition-state analogues have chemical features that have allowed them to be repurposed for new indications, including potential antiviral use. Three compounds from this family have entered clinical trials. The transition-state analogues bind to their target proteins with high affinity and specificity. The physical and structural properties of binding teach valuable and often surprising lessons about the nature of tight-binding inhibitors.
Keywords: Iminoribitols